International agreement in limiting the spread of nuclear weapons and its effect in the Middle East: Analysis from the Syariah Islamiyyah perspective / Alshima Mohammed Almlian - Alshima Mohammed, Almlian (2018)
This study aims to discover the Islamic view regarding the laws that limit the Nuclear proliferation. It turned out that the existence of legal rules and international conventions to limit the proliferation of nuclear weapons in the Middle East was primarily set to weaken the Arab and Islamic countries. Thus, the nuclear countries like Israel are going to control the wealth of the Islamic countries in the region. This led to an escalation in the regional and international tension and increased the fears of the use of these weapons and the occurrence of the third world war. In this study, the researcher explained the rules and provisions of the Shariah Rules of Islam which discusses the possessions and usage of lethal weapons and showed the conditions and rules which Muslims must follow when using these weapons, as the Muslim scholars worked on deriving principals on the legitimacy and permissibility of using lethal nuclear weapons that destroy the human and environment too. Through this study, the researcher clarified the legal rules and provisions regarding the possession, production and use of lethal weapons, and the restrictions and controls that Muslims must adhere to when using them. The scholars and jurists of the Islamic Nation worked on devising legal rulings, in the possession, production and use of lethal nuclear weapons that harm both humans and the environment. The researcher concluded that the origin of the international conventions and the motives behind their development is the interest and necessity of war and reciprocity, which is a legal and legitimate right, which is the opinion of the majority of Muslim jurists. It is carried out by some Muslim countries now, such as Turkey, Iran and Saudi Arabia. The study was conducted for the purpose of using the methodology of information gathering, using the analytical descriptive method, the inductive method, the deductive approach, and the comparative method.